2017
DOI: 10.1128/aac.01304-16
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Dosing Considerations for Gentamicin in Newborns with Suspected or Proven Sepsis Caused by Gram-Negative Bacteria

Abstract: The aim of this study was to describe the population pharmacokinetics (PK) of gentamicin in neonates with suspected or proven Gram-negative sepsis and determine the optimal dosage regimen in relation to the bacterial MICs found in this population. Data were prospectively collected between October 2012 and January 2013 in the Neonatal Intensive Care Unit (NICU) at the Academic Medical Center (AMC), Amsterdam, The Netherlands. A single nonlinear mixed-effects regression analysis (NONMEM) was performed to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In four studies with newborns, the impact of serum creatinine concentrations on gentamicin Cl was demonstrated . In contrast, five other studies (with newborns, infants, and children) failed to demonstrate a significant association between serum creatinine concentration and gentamicin Cl . In addition, two studies tested the association between creatinine Cl (calculated by the bedside Schwartz equation) and gentamicin Cl, and both studies detected a significant correlation .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In four studies with newborns, the impact of serum creatinine concentrations on gentamicin Cl was demonstrated . In contrast, five other studies (with newborns, infants, and children) failed to demonstrate a significant association between serum creatinine concentration and gentamicin Cl . In addition, two studies tested the association between creatinine Cl (calculated by the bedside Schwartz equation) and gentamicin Cl, and both studies detected a significant correlation .…”
Section: Discussionmentioning
confidence: 92%
“…In addition, in some recent studies, the influence of postmenstrual age (PMA) on gentamicin Cl was demonstrated because it describes the maturation of GFR better than other age‐related covariates. Furthermore, in one study, the influence of postconceptional age (PCA) in combination with Apgar score at 5 minutes (Apgar5) was examined, and it was found that Cl was reduced in newborns with PCA ≤ 34 weeks and Apgar5 < 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations